Internationalisation of higher education papers - Powar K B ed.; Roundtable on Internationalisation of Higher Education; Roundtable on internationalisation of higher education Amritsar, India 25-27 Feb 2002 (New Delhi Association of Indian Universities, 2002)
A second Roundtable on 'Internationalisation of Higher Education' was organized at Amritsar in February 2002. This publication includes the papers on the discussions of the Roundtable centered around the sub-themes
Keywords: Higher education